2020
DOI: 10.1016/j.psychres.2020.113108
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of the COVID-19 outbreak and lockdown among students and workers of a Spanish university

Abstract: The aim of this study was to analyze the psychological impact of COVID-19 in the university community during the first weeks of confinement. A cross-sectional study was conducted. The Depression Anxiety Stress Scale (DASS-21) was employed to assess symptoms of depression, anxiety and stress. The emotional impact of the situation was analyzed using the Impact of Event Scale. An online survey was fulfilled by 2530 members of the University of Valladolid, in Spain. Moderate to extremely severe scores of anxiety, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

89
760
19
80

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 897 publications
(948 citation statements)
references
References 22 publications
(27 reference statements)
89
760
19
80
Order By: Relevance
“…This study revealed that the prevalence of depression was 21.3%, which is in line with a review of existing literature (16-28%), 9 but lower than studies conducted in Pakistan (45%), Spain (34.1%), 12,13 and higher than Iran (15%) and India (13.97%). 14,15 The present study also indicated that the prevalence of anxiety was 27.1%, this finding is supported with a study done in China (24.9%) and review of existing literature (16-28%), 9,16 but higher than Iran (20%), India (12.63%) and Spain (21.3%), [13][14][15] and lower than a study done Jordan (69.5%), Pakistan (34%), France (60.2%), and Turkey (69.9%). 12,[17][18][19] Furthermore, this study also showed that the prevalence of stress was 32.5%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study revealed that the prevalence of depression was 21.3%, which is in line with a review of existing literature (16-28%), 9 but lower than studies conducted in Pakistan (45%), Spain (34.1%), 12,13 and higher than Iran (15%) and India (13.97%). 14,15 The present study also indicated that the prevalence of anxiety was 27.1%, this finding is supported with a study done in China (24.9%) and review of existing literature (16-28%), 9,16 but higher than Iran (20%), India (12.63%) and Spain (21.3%), [13][14][15] and lower than a study done Jordan (69.5%), Pakistan (34%), France (60.2%), and Turkey (69.9%). 12,[17][18][19] Furthermore, this study also showed that the prevalence of stress was 32.5%.…”
Section: Discussionsupporting
confidence: 89%
“…12,[17][18][19] Furthermore, this study also showed that the prevalence of stress was 32.5%. This result is supported with a study done in Spain (28.14%), 13 but higher than Indian (15.57%), 15 and lower than a study done in France (61.6%), and Jordan (69.5%). 17,18 The possible reason for the discrepancy might be due to difference in strict quarantine, high incidence rate, effect of lockdown, difference in literacy level and study sittings difference.…”
Section: Discussionsupporting
confidence: 79%
“…This unusual period of "suspension of classes and non-stop learning" [9] has had a negative effect on students globally. Previous studies have reported that national/regional lockdowns and travel restrictions have a negative effect on the mental health of students [10], and that these effects vary by age [11] and department [12]. Conversely, social support from family and partners is negatively associated with depression [10].…”
Section: Introductionmentioning
confidence: 98%
“…To assess stress resistance, we measured the number of social supports and SOC. As control variables, we included age, university department, and domicile status (living with family/a partner), which have been strongly associated with mental health outcomes in previous studies [10,11,12]. We analyzed the model goodness of t by gender, as gender is a determinant of stress recognition, choice of coping style [20], and symptoms of depression [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the factors associated with these behaviors and if they are impaired by the levels of stress these professionals have. A number of studies have assessed the psychological outcomes of the pandemic on health care workers [20][21][22] and the general population [23][24][25][26] but not on dental academics.…”
Section: Introductionmentioning
confidence: 99%